Atmospheric outflow of PM2.5 saccharides from megacity Shanghai to East China Sea: Impact of biological and biomass burning sources. (October 2016) - Li, Xiang; Chen, Minxuan; Le, Hoa Phuoc; Wang, Fengwen; Guo, Zhigang; Iinuma, Yoshiteru; Chen, Jianmin; Herrmann, Hartmut
Abstract: In an effort to more fully understand atmospheric outflow of PM2.5 -associated saccharide species, we investigated primary saccharides (fructose, glucose, sucrose, and trehalose), saccharide alcohols (arabitol and mannitol), and anhydrosaccharides (levoglucosan and mannosan) in atmospheric aerosols at both a megacity site, Shanghai, and a sea background site, Huaniao Island. The results showed that the saccharide species presented pronounced temporal and spatial variability in the outflow from the megacity to the East China Sea, and varied widely with a total concentration range of 8.6–2400 ng m −3 (283 ng m −3 mean) in Shanghai and 0–1050 ng m −3 (51 ng m −3 mean) in Huaniao Island. Both saccharide species (e.g., levoglucosan and sucrose) showed higher concentrations and a noticeable seasonal gradient during the study period ― there was a high level of levoglucosan in the cold season (161 ng m −3 in winter and 229 ng m −3 in autumn) due to elevated biomass burning activities, and a high level of sucrose in the warm seasons (146 ng m −3 in summer and 145 ng m −3 in spring) due to elevated levels of intense biological aerosols including fungal spores and pollen. The calculated levoglucosan/mannosan (L/M) ratio, which may represent the signature of aerosol particles at the two sites, ranged from 5.2 to 10.9 during the cold season. Back-trajectory analysis results indicated that the saccharides originated from regional sources in East and North China before being transported to the sampling site. Emissions due to biomass burning were estimated to correspond to 46% (mass) of the saccharides quantified in the haze particle samples, whereas biogenic emissions corresponded to 18%, indicating that biomass burning was a considerable aerosol source to the regional atmosphere throughout the year. The results presented here support the theory that levoglucosan could be utilized as a molecular marker for East Asian biomass burning outflow, and sucrose as a molecular marker for airborne pollen grains. The results of this study may help future researchers clarify the aerosol sources, as well as their atmospheric transport pathways over East Asia to the western Pacific Ocean. Highlights: Saccharides in the atmospheric outflow from megacity Shanghai to East China Sea. All PM2.5 saccharides show pronounced temporal and spatial variability in the outflow. Levoglucosan and sucrose dominate the total soluble saccharides. Biomass burning emissions are a significant source of saccharides in the outflow.